Wave Reversal Mode in Permalloy Wire-Tube Nanostructures - Escrig-Murua, J; Saavedra-Díaz, E (American Institute of Physics, 2022)
We have investigated hysteresis curves and magnetization reversal mechanisms in permalloy wire-tube nanostructures when an external magnetic field is applied perpendicular to the axis of the nanostructure, in the x direction. Our results show that the nanotube reverses its magnetization through the wave reversal mechanism, while the nanowire does so through pseudo-coherent rotation, according to the literature. The wire-tube nanostructure exhibits a more complex reversal mechanism, where each segment begins to revert depending on whether it is a wire or tube segment, but quickly the entire nanostructure adopts the wire segment reversal mechanism as its own, considerably reducing the area within of the hysteresis curve exhibited by the nanostructure. The possibility to alter the magnetization reversal mode in such nanostructures provides an attractive way to control the motion of the magnetic domain walls. © 2022 Author(s).